Evaluating Conservation Agriculture for Small-Scale Farmers in Sub-Saharan Africa and South Asia - Stevenson, James R.; Serraj, R.; Ed. Cassman, K.G. (Elsevier, 2014)
A set of papers from the ISPC strategic study on conservation agriculture (CA) has been published in a special issue of Agriculture, Ecosystems and Environment entitled “Evaluating conservation agriculture for small-scale farmers in Sub-Saharan Africa and South Asia”. The 13 papers in the issue give insight into the state of the science on CA across a range of disciplines - agronomy, economics, environmental science and social sciences. The papers were published together with an editorial by the ISPC.